Radiation dose analysis of large and giant internal carotid artery aneurysm treatment with the pipeline embolization device versus traditional coiling techniques. (8th April 2014) - Colby, Geoffrey P; Lin, Li-Mei; Nundkumar, Neelesh; Jiang, Bowen; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Background: Flow diversion is an effective and increasingly accepted method for endovascular treatment of cerebral aneurysms. Additionally, the public has heightened concerns regarding radiation exposure from medical procedures. This study analyzes radiation dose and fluoroscopy time during treatment of large and giant proximal internal carotid artery (ICA) aneurysms with the pipeline embolization device (PED) versus traditional coiling techniques. Methods: Radiation dose, fluoroscopy time, and contrast dye administration were retrospectively analyzed in 55 patients undergoing endovascular treatment of aneurysms ≥10 mm from petrous to superior hypophyseal ICA segments. Patients were treated by either PED (37 patients) or traditional coiling techniques (18 patients). Aortic arch type and proximal ICA tortuosity were also assessed as markers of access difficulty. Results: Average radiation dose with PED treatment was 2840±213 mGy and 4010±708 mGy with traditional coiling techniques (p=0.048; 29% decrease with PED). Mean fluoroscopy time for PED was 56.1±5.0 min and 85.9±11.9 min for coiling cases (p=0.0087; 35% decrease with PED). These benefits existed despite more difficult arch anatomy and a trend towards greater proximal vessel tortuosity in PED cases. Contrast dye amounts were also reduced by 37.5% in PED cases (75±6 mL) versus coiling cases (120±13 mL, p=0.0008). Conclusions: Treatment of large and giant proximal ICA aneurysms using PED requires less radiation, less fluoroscopy time, and less contrast administration than standard coiling techniques. This further demonstrates the benefits of flow diversion for treatment of these aneurysms.